Flat Structure, Equitable Rewards, and Employee Performance: The Mediating Role of OCB - Putu Alit Wardana; I Gusti Ayu Wimba; I Made Astrama (UNIVERSITAS PGRI MADIUN, 2026)
This study investigates the impact of Slim Organizational Structure and Proportional Reward on employee performance, with Organizational Citizenship Behavior (OCB) as a mediating variable, at PT Ananta Widhya Husada in Badung, Bali. Using a quantitative approach, data were collected through questionnaires from 89 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results demonstrate that Slim Organizational Structure has a significant positive effect on both OCB (? = 0.534; t = 7.582; p < 0.001) and employee performance (? = 0.304; t = 3.018; p < 0.01). Similarly, Proportional Reward significantly influences OCB (? = 0.336; t = 2.173; p < 0.05) and employee performance (? = 0.552; t = 1.980; p < 0.05). OCB itself exerts a strong positive impact on employee performance (? = 0.476; t = 5.049; p < 0.001), and it partially mediates the effect of Slim Organizational Structure on performance but does not mediate the effect of Proportional Reward. These findings highlight the importance of organizational design and fair reward systems in shaping employee behavior and productivity, while also clarifying the distinct role of OCB as a behavioral mechanism in enhancing performance outcomes within healthcare organizations.